2018
DOI: 10.1149/08513.0129ecst
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Computational Fluid Dynamic Modeling of the Resistivity and Overpotential in Reverse Electrodialysis

Abstract: The resulting electrical potential of a reverse electrodialysis is reduced both due to ohmic and non-ohmic resistances. The nonohmic resistance is mainly controlled by concentration polarization which is a considerable challenge in a membrane based processes and is a result of accumulation or depletion of specific ions adjacent to the ionic exchange membranes compared to the bulk solution. This phenomenon effectively reduces the driving force across the membrane, hence affects the performance of the process. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…The cell resistance (mostly) increases with decreasing dilute concentration due to the decrease in the resistance of the dilute flow compartment. Jalili et al [46] simulated the resistance in the flow compartments in RED using OpenFOAM, where they found the resistance to be 0.4 mΩ m 2 and 0.04 mΩ m 2 for the dilute and concentrated solutions, respectively. These calculations are similar to our total calculated resistance.…”
Section: Stack Measurementsmentioning
confidence: 99%
“…The cell resistance (mostly) increases with decreasing dilute concentration due to the decrease in the resistance of the dilute flow compartment. Jalili et al [46] simulated the resistance in the flow compartments in RED using OpenFOAM, where they found the resistance to be 0.4 mΩ m 2 and 0.04 mΩ m 2 for the dilute and concentrated solutions, respectively. These calculations are similar to our total calculated resistance.…”
Section: Stack Measurementsmentioning
confidence: 99%
“…They observed that the spacer area fraction had a dominant effect only for less porous spacers [ 30 ]. Jalili et al [ 31 , 32 ] used CFD modeling to examine the influence of flow velocities and spacer topology with respect to the transport of mass and momentum, as well as the flow channel resistivity of a RED unit cell. They reported that the resistivity of the dilute solution channel dominates over the resistivity of the concentrated solution channel and membranes in a RED unit cell [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations have also been reported by Ortiz-Martinez et al [ 33 ]. The electrical potential of a RED unit cell was enhanced by reducing the flow velocity and introducing flow promoters in a dilute solution channel, due to reduced solution resistance [ 32 ]. Introducing spacers in a concentrated solution channel or increasing the flow velocity in a dilute solution channel increases the resistivity and has adverse effects on the electrical potential [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations